Morphological and Cultural and Variation of Exserohilum turcicum isolates in Sorghum (Sorghum bicolour L.) - Rajula , Julius; J. Ochuodho, J. Ochuodho; E. K., Kiprop (African Journal of Education,Science and Technology (AJEST), 2017)
Sorghum is mainly cultivated for human consumption. Although it is considered as the second most important cereal crop after maize in Africa, this crop is affected by various diseases due to availability of hybrids that are susceptible. Therefore, this research is aimed at characterizing Exserohilum turcicum that is a causative agent of Turcicum leaf blight in Western region of Kenya using cultural and morphological characteristics. Diseased leaf samples of sorghum were collected from two regions (Kibos and Sega) in Western region of Kenya. A number of 6 fungal isolates were studied for both cultural (colony color, pigmentation, sporulation and growth pattern) and morphological (conidia) properties after twelve days of growth on PDA at 25 0C. Cultural characteristics did show that there was variation among isolates of E. turcicum in colony growth and colour. The colony color was categorized into three categories i.e. gray, dark gray and golden brown. Based on colony pigmentation, the isolates were grouped into black and brown. Based on sporulation, the isolates were classified as; profuse, moderate and fair. On the other hand, the conidial shapes were observed to be curved and fusiform-elliptical. Results also showed significant variations in conidial size, length and width and number of septa in the six isolates of E. turcicum. The largest conidia were reported for isolate Western 1 (103 µm in length and 23.86 µm in width). The average number of septa was 4.5 (range 3-6 septa). Isolates from the two study regions reported similar cultural and morphological characteristics. The characteristics studied which were morphological and cultural showed that, the isolates were E. turcicum. The results of this study will serve as a model for other studies in the future and will also assist in coming up with mitigating losses in sorghum yield.